Innovative Eco-Friendly Methyl Orange Removal: Mechanism, Kinetic, and Thermodynamic Study Using Starch Cryogel-Integrated Mesoporous Silica Nanoparticles - Tarawee Taweekarn; Worawit Wongniramaikul; Wilasinee Sriprom; Wadcharawadee Limsakul; Chanadda Phawachalotorn; Aree Choodum (My University, 2024)
This study introduces a novel, eco-friendly composite, uncalcined mesoporous silica nanoparticles incorporated into a starch cryogel (MSNs-Cry), designed for the effective removal of methyl orange (MO) from water. MSNs-Cry integrates uncalcined mesoporous silica nanoparticles (MSNs) within a starch cryogel network, leveraging the high adsorption capacity of MSNs. The composite achieved a maximum adsorption capacity of 18.98 mg g⁻
Keywords: Methyl orange; Modified starch; Environmentally Friendly; Water Quality Monitoring and Analysis